Changing Business Dynamism and Productivity: Shocks versus Responsiveness - Decker, Ryan A.; Haltiwanger, John; Jarmin, Ron S.; Miranda, Javier (American Economic Review, 2020)
The pace of job reallocation has declined in the United States in recent decades. We draw insight from canonical models of business dynamics in which reallocation can decline due to (i ) lower dis persion of idiosyncratic shocks faced by businesses, or (ii ) weaker marginal responsiveness of businesses to shocks. We show that shock dispersion has actually risen, while the responsiveness of business-level employment to productivity has weakened. Moreover, declining responsiveness can account for a significant fraction of the decline in the pace of job reallocation, and we find suggestive evidence this has been a drag on aggregate productivity. (JEL D24, E24, E32, J21, J23, J24, L60)